A new ordered compactification - D. C. Kent; T. A. Richmond (International Journal of Mathematics and Mathematical Sciences)
A new Wallman-type ordered compactification γ∘X is constructed using maximal CZ-filters (which have filter bases obtained from increasing and decreasing zero sets) as the underlying set. A necessary and sufficient condition is given for γ∘X to coincide with the Nachbin compactification β∘X; in particular γ∘X=β∘X whenever X has the discrete order. The Wallman ordered compactification ω∘X equals γ∘X whenever X is a subspace of Rn. It is shown that γ∘X is always T1, but can fail to be T1-ordered or T2.